2019
DOI: 10.1111/jpc.14429
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and emotional problems among school children in Pakistan: A telephonic survey for prevalence and risk factors

Abstract: Aim Escalating rates of childhood mental health disorders constitute a serious issue for countries like Pakistan. However, due to a scarce number of studies on childhood behavioural problems, understanding the magnitude and gap of the problem is a challenge. Thus, the present study is intended to bridge this gap. This study provides estimates for prevalence, associated demographic risk factors and the impact of behavioural and emotional problems among school children. Methods A sample of children (n = 800) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
(74 reference statements)
2
9
1
1
Order By: Relevance
“…23 The high prevalence of conduct disorder could be associated with many factors as the child has to continually deal with the loss of parents, proper care and guidance, and social discrimination. 24 In this study, the overall SDQ score with regard to gender was insignificant; however, considering individual domain, the mean score of the males was significantly (p < 0.05) associated with the conduct disorder while females were found to have a significant relationship with a higher ratio of emotional disorders. Similar to these findings, studies from Kenya and India also found that the girls reported more internalizing problems than the boys.…”
Section: Discussioncontrasting
confidence: 50%
“…23 The high prevalence of conduct disorder could be associated with many factors as the child has to continually deal with the loss of parents, proper care and guidance, and social discrimination. 24 In this study, the overall SDQ score with regard to gender was insignificant; however, considering individual domain, the mean score of the males was significantly (p < 0.05) associated with the conduct disorder while females were found to have a significant relationship with a higher ratio of emotional disorders. Similar to these findings, studies from Kenya and India also found that the girls reported more internalizing problems than the boys.…”
Section: Discussioncontrasting
confidence: 50%
“…In a systematic review from Bangladesh, the prevalence of mental disorders was found to range from 13.4% to 22.9% among children aged 2–16 [ 11 ]. In Pakistan, a study among school children aged 6–16 reported a prevalence of 15.9% of behavior problems and 22.5% of emotional problems [ 12 ]. In another LMIC country, Iran, a community-based study of children aged 6–17 reported a prevalence rate of 16.7% of total difficulties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison there is dearth of research in non-Western cultures and low and middle-income countries like Pakistan (e.g., McCoy et al, 2016); and no research has examined this constellation of factors in Pakistani samples. Where similar research on Pakistani children does exist, it is concerned primarily with quantifying the presence of emotional and behavior problems in older children (e.g., Hussein, 2010;Malik et al, 2019;Syed & Hussein, 2009; for exception, see Finch et al, 2018) interventions (e.g., Inam et al, 2015;Zainulabdin, 2020). Country vides statistics indicate that more than a quarter of Pakistani preschoolers' social-emotional skills are at a low level, this is indexed by high level of aggression, distraction and low or poor social competence on ECDI (Early Childhood Development Index) (Flinch et al, 2018) As Pakistani parents and the broader society observe that children's refusal to go to school, absenteeism, and school dropout are on the rise (Malik et al, 2019), research on the importance of temperament and its consequent social and school adjustment is both timely and important.…”
Section: Studies In Pakistanmentioning
confidence: 99%